Evaluation of ingredient combinations from differing origins (fishmeal, terrestrial animal and plants) and two different formulated nutrient targets on rainbow trout growth and production efficiency. (22nd February 2017) - Gaylord, T.G.; Sealey, W.M.; Barrows, F.T.; Myrick, C.A.; Fornshell, G.
Abstract: A 12‐week trial was performed with rainbow trout ( Oncorhynchus mykiss ) utilizing combinations of ingredients at two nutrient targets. Ingredient combinations were fishmeal‐based diet (FMD), animal product‐based diet (APD), plant product‐based diet (PPD), novel plant‐based diet (NPD) and potential future plant‐based diet (FPD). Two nutrient concentrations were targeted: 1) to meet published amino acid targets for rainbow trout utilizing approximately 450 g/kg crude protein (400–420 g/kg digestible protein) and 2) to meet the amino acid targets based on ideal amino acid balance of trout muscle for Lys, Met and Thr utilizing approximately 400 g/kg crude protein (370–380 g/kg digestible protein). Interactive effects between ingredient combination and nutrient concentration occurred across all response variables. When diets were formulated to Target 1, fish consuming FMD and APD displayed better weight gain and feed conversion ratio (FCR) than plant‐based diet, while graded effects were found within the plant‐based treatments. When differing ingredient combinations were utilized and formulated to Target 2, fish grew equally well except for the NPD treatment which supported lower growth and higher FCR. Based on the data from the current experiment, one can completely remove fishmeal from trout feeds and reduce protein levels when dietary digestible amino acids are balanced.